ESD-Based Project-Based Learning Enhances Science Literacy Among Senior High School Students - Desyta, Lila; Safriana, Safriana; Siska, Deassy; Andriani, Riza (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2027)
This study investigated the effect of implementing Project-Based Learning (PjBL) integrated with Education for Sustainable Development (ESD) on the science literacy of Grade X students at MAS Syamsuddhuha. A quantitative quasi-experimental design with a nonequivalent control group was used. The experimental group received PjBL-ESD through a contextual project on converting organic waste to biogas, while the control group received conventional instruction. Instruments included a validated nine-item essay test based on the PISA science literacy framework, observation sheets for learning implementation, and student interview guides. Quantitative data were tested for normality and homogeneity, then analyzed using Independent Samples t-test and Cohen’s d for effect size; qualitative data were analyzed descriptively. Results showed a significant improvement in the experimental group’s posttest mean score (90.44) compared to the control group (74.00), p < 0.001. The effect size was very large (Cohen’s d = 2.5), indicating substantial practical impact. Observation results indicated complete and high-quality implementation (100%, Very Good), and interviews revealed positive student responses along with strengthened scientific attitudes and awareness of environmental sustainability. The study concludes that PjBL integrated with ESD effectively enhances science literacy among high school students, even in contexts with limited laboratory facilities; it is recommended as a contextual and sustainable instructional strategy for renewable energy topics.